Optical characteristics of the nanoparticle coupled to a quantum molecular aggregate - Ropakova, I.Yu.; Zvyagin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Optical characteristics of a single nanoparticle, coupled to the one-dimensional quantum molecular aggregate is studied. Depending on the values of the coupling of the particle and its own frequency, with respect to the own frequency of the aggregated molecules, and the strength of the aggregation, the dynamical relative permittivity of the nanoparticle manifests the contribution from the exciton band, or/and the ones from the local level(s) caused by the particle. The refractive index and the extinction coefficient of the nanoparticle is also calculated.